1999
DOI: 10.1021/bi991287j
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman Studies of Cytochrome P450bm3 and Its Complexes with Exogenous Ligands

Abstract: Resonance Raman spectra are reported for both the heme domain and holoenzyme of cytochrome P450BM3 in the resting state and for the ferric NO, ferrous CO, and ferrous NO adducts in the absence and presence of the substrate, palmitate. Comparison of the spectrum of the palmitate-bound form of the heme domain with that of the holoenzyme indicates that the presence of the flavin reductase domain alters the structure of the heme domain in such a way that water accessibility to the distal pocket is greater for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
51
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 41 publications
22
51
2
Order By: Relevance
“…The same spectral pattern was observed for HuCYP51. These observed frequencies of the marker lines in the two CYP51s were almost identical to those in CYP101, CYP102, and CYP121, which indicates that the heme of CYP51s are planar as found for other CYP enzymes (37)(38)(39).…”
Section: Resultssupporting
confidence: 59%
“…The same spectral pattern was observed for HuCYP51. These observed frequencies of the marker lines in the two CYP51s were almost identical to those in CYP101, CYP102, and CYP121, which indicates that the heme of CYP51s are planar as found for other CYP enzymes (37)(38)(39).…”
Section: Resultssupporting
confidence: 59%
“…On the other hand, we and others have shown that the nature of the guanidine substrate can significantly modify the oxidation chemistry, along with the resulting reaction intermediates and products (41,42,71,72). These considerations led us to address, in this work, the actual role of the guanidinium proton in the mechanism of NOS by analyzing the interactions between the heme active site and the guanidinium moiety of L (41, 55-57, 59, 69, 70) and cytochromes P450 (44,68,(73)(74)(75)(76). In addition to bond angles, the Fe-CO vibrational modes are very sensitive to the electrostatic and polar properties of the heme distal pocket because of changes in the back donation from the iron d* orbital to the empty * CO orbital (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the ν N−O mode is usually not resonance enhanced with Soret excitation [38], we could not localize this mode in the high-frequency region of the FeIII-NO spectra using isotope substitution (results not shown). [24,40], iNOSox [24,41], P450 nor [42] and P450 BM3 [43]. The line at 539 cm −1 ( 4 cm −1 ) of saNOS was thus assigned to the ν Fe−NO mode.…”
Section: High-frequency Region Of the Feiii-no Complexes Of Sanos Andmentioning
confidence: 96%
“…The frequencies of the ν Fe−NO modes of saNOS (539 cm −1 ) and bsNOS (540 cm −1 ) in the absence of substrate and H 4 B were nearly identical, indicating that both proteins had very similar haem environments. These frequencies were compared with those of other haem proteins and were found to most resemble those of nNOSox (535 cm −1 ) and iNOSox (537 cm −1 ) rather than P450 cam (528 cm −1 ; [39]) and P450 BM3 (526 cm −1 ; [43]), indicating a similar environment at the active sites of bacterial and mammalian NOSs ( Table 1). The frequencies of the ν Fe−NO modes of saNOS and bsNOS were insensitive to the addition of the pterins H 4 B and THF (Table 1).…”
Section: Low-frequency Region Of the Feii-no Complexes Of Sanos And Bmentioning
confidence: 99%